Anti-crack baseball bat and process method thereof

By adopting a six-layer structure crack-resistant baseball bat design, the combination of modified carbon fiber, glass fiber and composite adhesive layer is solved, and the problem of insufficient crack resistance and toughness is achieved. , improves players' safety and batting success rate.

CN119391314APending Publication Date: 2025-02-07TIANCHANG ZHENGMU ALUMINUM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411657906.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing baseball bats are prone to cracks during batting, which affects the safety of players and the success rate of hitting, and the crack resistance of composite baseball bats is insufficient.

Method used

The crack-resistant baseball bat design is adopted with a six-layer structure from the inside to the outside, including a modified carbon fiber layer, a glass fiber layer, a composite adhesive layer, etc. The mechanical properties and toughness of the material are enhanced by the combination of modified fibers and resins.

Benefits of technology

It improves the crack resistance and toughness of the baseball bat, reduces the risk of cracks when hitting, and enhances the player's sense of security and hitting success rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391314A_ABST
    Figure CN119391314A_ABST
Patent Text Reader

Abstract

The invention provides an anti-crack baseball bat and a technological method thereof, and relates to the technical field of baseball bat. An anti-crack baseball bat comprises a first fiber layer, a first isolation layer, a second fiber layer, a second isolation layer, a third fiber layer and a composite adhesive film layer from inside to outside. According to the anti-cracking baseball bat, through the mutual synergistic effect of the raw materials and the technological method, the prepared anti-cracking baseball bat has the performance of high strength and light weight, and the requirements of modern sports goods are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of baseball bats, in particular to an anti-cracking baseball bat and a process method thereof. Background Art

[0002] A baseball bat is a tool used by batters in baseball to hit the ball. Common materials include wood, aluminum, and composite materials. Composite baseball bats can effectively reduce the discomfort when hitting the ball due to their excellent shock absorption properties, which is very important for players who play or train for a long time. Secondly, composite baseball bats usually have a larger sweet spot, which means that it is easier for players to hit the ball when swinging, thereby increasing the success rate of hitting the ball, making them very popular in baseball. In addition, the crack resistance of a baseball bat is also one of the key properties of a baseball bat, and crack resistance is an important factor in ensuring the safety of players. Therefore, it is urgent to develop a crack-resistant baseball bat and its process method, which is of great significance for the practical application of baseball bats. Summary of the invention

[0003] Based on the technical problems existing in the background technology, the present invention proposes an anti-cracking baseball bat and a process method thereof.

[0004] The anti-cracking baseball bat provided by the present invention comprises, from inside to outside, a first fiber layer, a first isolation layer, a second fiber layer, a second isolation layer, a third fiber layer, and a composite adhesive film layer.

[0005] Preferably, the first fiber layer comprises modified carbon fibers and resin slurry.

[0006] More preferably, the method for preparing the modified carbon fiber comprises the following steps:

[0007] The carbon fiber is ultrasonically treated in an ethanol mixed solution and dried to obtain pretreated carbon fiber; the pretreated carbon fiber is immersed in an N-(2-aminoethyl)-3-aminopropyltrimethoxysilane solution, taken out and dried to obtain modified carbon fiber.

[0008] More preferably, the ethanol mixed solution comprises ethanol, acetone and water, and the mass ratio of ethanol, acetone and water is 1:(1-2):1.

[0009] More preferably, the mass fraction of the N-(2-aminoethyl)-3-aminopropyltrimethoxysilane solution is 1-8wt%.

[0010] More preferably, the ultrasonic frequency of the ultrasonic treatment is 15-40 Hz, and the ultrasonic power density is 0.5-1 W / cm 2 .

[0011] The modification treatment of carbon fiber includes cleaning, drying and surface modification activation, which removes impurities on the surface of carbon fiber and makes the carbon fiber have good adhesion and wettability.

[0012] More preferably, the resin slurry comprises the following raw materials in parts by weight: 100 parts of epoxy resin, 10-50 parts of bismaleimide resin, 1-10 parts of curing agent, and 5-10 parts of nano clay.

[0013] The present invention adds different resins and auxiliary materials into the resin slurry to jointly improve the processing performance and mechanical properties of the material.

[0014] Preferably, the second fiber layer comprises glass fiber and epoxy resin.

[0015] Preferably, the third fiber layer includes third fibers and epoxy resin.

[0016] More preferably, the third fiber is selected from one or more of carbon fiber, glass fiber, modified carbon fiber, and polyimide fiber.

[0017] The three fiber layers of the present invention are constructed by selecting different fibers. The first fiber layer is combined with modified carbon fiber and resin slurry to obtain a first fiber layer with excellent mechanical properties. As a rigid fiber bottom layer material, it ensures the crack resistance of the baseball bat. The second fiber layer is used as the middle layer of the baseball bat and can play a buffering role during the baseball bat hitting the ball. In addition, the outermost third fiber layer selects different fibers as composite fibers and the composite adhesive film layer to cooperate with each other to ensure the toughness of the baseball bat, absorb energy, eliminate internal stress, and prevent cracks.

[0018] Preferably, the first isolation layer and the second isolation layer are BOPP.

[0019] In the present invention, BOPP mainly plays the role of isolation and delamination in the crack-resistant baseball bat.

[0020] Preferably, the composite adhesive film layer comprises the following raw materials in parts by weight: 75-115 parts of resin, 20-50 parts of rubber, 4-9 parts of curing agent, 2-15 parts of auxiliary agent, 1-7 parts of silane coupling agent, and 0.1-1 parts of carbon fiber powder.

[0021] More preferably, the resin is selected from one or more of bisphenol A epoxy resin, p-aminophenol epoxy resin, and diglycidyl isophthalate.

[0022] More preferably, the mass ratio of the bisphenol A epoxy resin, p-aminophenol epoxy resin, and diglycidyl isophthalate is (2-4):1:1.

[0023] More preferably, the rubber is selected from one or more of hydroxyl-terminated liquid silicone rubber, liquid carboxyl-terminated nitrile rubber, and core-shell rubber microspheres.

[0024] More preferably, the core of the core-shell rubber microsphere comprises polybutadiene, acrylic rubber or silicon dioxide, and the shell comprises polystyrene, polyurethane or polymethyl methacrylate.

[0025] More preferably, the curing agent is selected from one or more of dicyandiamide and diaminodiphenylmethane.

[0026] More preferably, the auxiliary agent is selected from one or more of a promoter and a stabilizer.

[0027] More preferably, the accelerator is selected from one or more of 2-phenylimidazoline and 2-ethyl-4-methylimidazole.

[0028] More preferably, the stabilizer is zinc acetyl-2-hydroxyisobutyrate.

[0029] More preferably, the silane coupling agent is γ-aminopropyltriethoxysilane.

[0030] The composite adhesive film layer of the present invention comprises resin, rubber, curing agent, auxiliary agent, silane coupling agent and carbon fiber powder. The composite adhesive film layer obtained by adjusting the formula has synergistic effects between the raw materials, so that the composite adhesive film layer has toughness and certain crack resistance. The present invention ensures that the rubber is evenly distributed and firmly bonded by reacting the resin with the rubber to form a two-phase network structure with tight and loose alternations. When the material is impacted, the rubber phase can disperse the stress, thereby improving the impact toughness and effectively avoiding the cracking of the baseball bat.

[0031] Preferably, the preparation of the composite adhesive film layer comprises the following steps: melting, blending, extruding, granulating and pressing the raw materials to obtain the composite adhesive film layer.

[0032] The present invention also provides a process for making a crack-resistant baseball bat, comprising the following steps:

[0033] S1, wrapping the modified carbon fiber impregnated with resin slurry on a core mold to obtain a first fiber layer;

[0034] S2, wrapping the first fiber layer in sequence with a first isolation layer, a second fiber layer, a second isolation layer, a third fiber layer, and a composite adhesive film layer to obtain a preform;

[0035] S3, curing the preform, demoulding from the core mold, and obtaining a crack-resistant baseball bat.

[0036] Preferably, the impregnation is fully achieved by applying pressure during the impregnation process.

[0037] Preferably, in S1, the core mold is used to form a hollow structure of a baseball bat; the core mold includes an air nozzle, an outer skin layer and an internal bracket to ensure that it has good air tightness and structural stability.

[0038] Preferably, in S1 and S2, the wrapping method is pultrusion or winding.

[0039] Preferably, in S3, the curing treatment comprises first treating at a temperature of 80-100° C. and a pressure of 8-10 MPa for 5-10 min, and then treating at a temperature of 140-150° C. and a pressure of 10-12 MPa for 35-40 min.

[0040] The impregnated fiber preform is heated and cured to form a cross-linked structure in the resin matrix, thereby improving the mechanical properties and chemical stability of the prepreg.

[0041] The beneficial effects of the present invention are:

[0042] The present invention proposes an anti-crack baseball bat, which includes a first fiber layer, a first isolation layer, a second fiber layer, a second isolation layer, a third fiber layer, and a composite film layer from the inside to the outside. The synergistic effect between each layer makes the obtained anti-crack baseball bat not only have excellent rigidity, but also have certain toughness, and is not easy to break during the batting process. The present invention modifies the fibers of the fiber layer so that the fiber layer has excellent mechanical properties and durability; in addition, the third fiber layer and the composite film layer are tightly combined to form a whole, which absorbs energy, eliminates internal stress, and prevents cracks from occurring when subjected to external force. The anti-crack baseball bat of the present invention is prepared through the synergistic effect of raw materials and process methods, and has high strength and light weight, meeting the needs of modern sporting goods. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 A cross-sectional view of the anti-crack baseball bat proposed by the present invention;

[0044] 1-first fiber layer, 2-first isolation layer, 3-second fiber layer, 4-second isolation layer, 5-third fiber layer, 6-composite adhesive film layer. DETAILED DESCRIPTION

[0045] The technical solution of the present invention is described in detail through specific embodiments.

[0046] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0047] Example 1

[0048] A crack-resistant baseball bat comprises, from inside to outside, a first fiber layer, a first isolation layer, a second fiber layer, a second isolation layer, a third fiber layer, and a composite adhesive film layer.

[0049] The first fiber layer includes modified carbon fibers and resin slurry.

[0050] The preparation method of modified carbon fiber comprises the following steps:

[0051] The carbon fiber is ultrasonically treated in an ethanol mixed solution and dried to obtain a pretreated carbon fiber; the pretreated carbon fiber is immersed in an N-(2-aminoethyl)-3-aminopropyltrimethoxysilane solution, taken out and dried to obtain a modified carbon fiber; the ethanol mixed solution is composed of ethanol, acetone and water in a mass ratio of 1:2:1; the mass fraction of the N-(2-aminoethyl)-3-aminopropyltrimethoxysilane solution is 3wt%; the ultrasonic frequency of the ultrasonic treatment is 25Hz, and the ultrasonic power density is 0.5W / cm 2 .

[0052] The resin slurry includes the following raw materials in parts by weight: 100 parts of epoxy resin, 35 parts of bismaleimide resin, 5 parts of curing agent, and 8 parts of nano clay.

[0053] The second fiber layer includes glass fiber and epoxy resin.

[0054] The third fiber layer includes third fibers and epoxy resin; the third fibers are composed of glass fibers, modified carbon fibers, and polyimide fibers in a mass ratio of 1:3:0.5.

[0055] The first isolation layer and the second isolation layer are BOPP.

[0056] The composite adhesive film layer comprises the following raw materials in parts by weight: 90 parts of resin, 35 parts of rubber, 5 parts of curing agent, 4 parts of auxiliary agent, 3 parts of γ-aminopropyl triethoxysilane, and 0.5 parts of carbon fiber powder; the resin is composed of bisphenol A epoxy resin, p-aminophenol epoxy resin, and diglycidyl isophthalate in a mass ratio of 3:1:1; the rubber is composed of hydroxyl-terminated liquid silicone rubber, liquid carboxyl-terminated nitrile rubber, and silica-polymethyl methacrylate core-shell rubber microspheres in a mass ratio of 2:2:0.5; the curing agent is composed of dicyandiamide and diaminodiphenylmethane in a mass ratio of 1:1; the auxiliary agent includes 2 parts of 2-ethyl-4-methylimidazole and 2 parts of acetyl-2-hydroxyisobutyric acid.

[0057] The preparation of the composite adhesive film layer comprises the following steps: melting, blending, extruding, granulating and pressing the raw materials to obtain the composite adhesive film layer.

[0058] A process for making a crack-resistant baseball bat comprises the following steps:

[0059] S1, wrapping the modified carbon fiber impregnated with resin slurry on a core mold to obtain a first fiber layer;

[0060] S2, wrapping the first fiber layer in sequence with a first isolation layer, a second fiber layer, a second isolation layer, a third fiber layer, and a composite adhesive film layer to obtain a preform;

[0061] S3, curing the preform, demolding it from the core mold, and obtaining a crack-resistant baseball bat; the curing treatment includes first treating it at a temperature of 80° C. and a pressure of 10 MPa for 5 minutes, and then treating it at a temperature of 140° C. and a pressure of 12 MPa for 35 minutes.

[0062] The second fiber layer and the third fiber layer are composed of fibers pre-impregnated with epoxy resin.

[0063] Example 2

[0064] A crack-resistant baseball bat comprises, from inside to outside, a first fiber layer, a first isolation layer, a second fiber layer, a second isolation layer, a third fiber layer, and a composite adhesive film layer.

[0065] The first isolation layer, the second fiber layer, the third isolation layer, and the third fiber layer are the same as those in Example 1.

[0066] The first fiber layer includes modified carbon fibers and resin slurry.

[0067] The preparation method of the modified carbon fiber is the same as that of Example 1; the resin slurry includes the following raw materials in parts by weight: 100 parts of epoxy resin, 20 parts of bismaleimide resin, 5 parts of curing agent, and 10 parts of nano clay.

[0068] The composite adhesive film layer comprises the following raw materials in parts by weight: 95 parts of resin, 20 parts of rubber, 4 parts of curing agent, 4 parts of auxiliary agent, 3 parts of γ-aminopropyl triethoxysilane, and 0.5 parts of carbon fiber powder; the resin is composed of bisphenol A epoxy resin, p-aminophenol epoxy resin, and diglycidyl isophthalate in a mass ratio of 3:1:1; the rubber is composed of hydroxyl-terminated liquid silicone rubber, liquid carboxyl-terminated nitrile rubber, and silica-polymethyl methacrylate core-shell rubber microspheres in a mass ratio of 2:2:1; the curing agent is composed of dicyandiamide and diaminodiphenylmethane in a mass ratio of 1:1; the auxiliary agent includes 2 parts of 2-ethyl-4-methylimidazole and 2 parts of acetyl-2-hydroxyisobutyric acid.

[0069] The preparation of the composite film layer is the same as that in Example 1.

[0070] The process for producing a crack-resistant baseball bat is the same as that of Example 1.

[0071] Example 3

[0072] A crack-resistant baseball bat comprises, from inside to outside, a first fiber layer, a first isolation layer, a second fiber layer, a second isolation layer, a third fiber layer, and a composite adhesive film layer.

[0073] The first isolation layer, the second fiber layer, the third isolation layer, and the third fiber layer are the same as those in Example 1.

[0074] The first fiber layer includes modified carbon fibers and resin slurry.

[0075] The preparation method of the modified carbon fiber is the same as that of Example 1; the resin slurry includes the following raw materials in parts by weight: 100 parts of epoxy resin, 27 parts of bismaleimide resin, 5 parts of curing agent, and 10 parts of nano clay.

[0076] The composite adhesive film layer comprises the following raw materials in parts by weight: 90 parts of resin, 30 parts of rubber, 4 parts of curing agent, 4 parts of auxiliary agent, 3 parts of γ-aminopropyl triethoxysilane, and 0.5 parts of carbon fiber powder; the resin is composed of bisphenol A epoxy resin, p-aminophenol epoxy resin, and diglycidyl isophthalate in a mass ratio of 3:1:1; the rubber is composed of hydroxyl-terminated liquid silicone rubber, liquid carboxyl-terminated nitrile rubber, and silica-polymethyl methacrylate core-shell rubber microspheres in a mass ratio of 2:2:0.5; the curing agent is composed of dicyandiamide and diaminodiphenylmethane in a mass ratio of 1:1; the auxiliary agent includes 2 parts of 2-ethyl-4-methylimidazole and 2 parts of acetyl-2-hydroxyisobutyric acid.

[0077] The preparation of the composite film layer is the same as that in Example 1.

[0078] The process for producing a crack-resistant baseball bat is the same as that of Example 1.

[0079] Example 4

[0080] A crack-resistant baseball bat comprises, from inside to outside, a first fiber layer, a first isolation layer, a second fiber layer, a second isolation layer, a third fiber layer, and a composite adhesive film layer.

[0081] The first isolation layer, the second fiber layer, the third isolation layer, and the third fiber layer are the same as those in Example 1.

[0082] The first fiber layer includes modified carbon fibers and resin slurry.

[0083] The preparation method of the modified carbon fiber is the same as that of Example 1; the resin slurry includes the following raw materials in parts by weight: 100 parts of epoxy resin, 50 parts of bismaleimide resin, 5 parts of curing agent, and 5 parts of nano clay.

[0084] The composite adhesive film layer comprises the following raw materials in parts by weight: 90 parts of resin, 30 parts of rubber, 4 parts of curing agent, 4 parts of auxiliary agent, 3 parts of γ-aminopropyltriethoxysilane, and 0.5 parts of carbon fiber powder; the resin is composed of bisphenol A epoxy resin, p-aminophenol epoxy resin, and diglycidyl isophthalate in a mass ratio of 3:1:1; the rubber is composed of hydroxyl-terminated liquid silicone rubber and liquid carboxyl-terminated nitrile rubber in a mass ratio of 1:1; the curing agent is composed of dicyandiamide and diaminodiphenylmethane in a mass ratio of 1:1; the auxiliary agent includes 2 parts of 2-ethyl-4-methylimidazole and 2 parts of acetyl-2-hydroxyisobutyric acid.

[0085] The preparation of the composite film layer is the same as that in Example 1.

[0086] The process for producing a crack-resistant baseball bat is the same as that of Example 1.

[0087] The above crack-resistant baseball bat was tested for its bending strength, elongation at break, compressive strength, and tensile strength. The test results are shown in Table 1.

[0088] Table 1

[0089]

[0090] It can be seen from the data in Table 1 that the crack-resistant baseball bat prepared by the present invention has excellent performance.

[0091] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A crack-resistant baseball bat, characterized in that: From inside to outside, it includes a first fiber layer, a first isolation layer, a second fiber layer, a second isolation layer, a third fiber layer, and a composite adhesive film layer.

2. The anti-crack baseball bat according to claim 1, characterized in that: The first fiber layer includes modified carbon fibers and resin slurry.

3. The anti-crack baseball bat according to claim 2, characterized in that: The preparation method of the modified carbon fiber comprises the following steps: ultrasonically treating the carbon fiber in an ethanol mixed solution and drying to obtain pretreated carbon fiber; immersing the pretreated carbon fiber in an N-(2-aminoethyl)-3-aminopropyltrimethoxysilane solution, taking out and drying to obtain the modified carbon fiber.

4. The anti-crack baseball bat according to claim 2, characterized in that: The resin slurry comprises the following raw materials in parts by weight: 100 parts of epoxy resin, 10-50 parts of bismaleimide resin, 1-10 parts of curing agent, and 5-10 parts of nano clay.

5. The crack-resistant baseball bat according to claim 1, characterized in that: The second fiber layer includes glass fiber and epoxy resin.

6. The crack-resistant baseball bat according to claim 1, characterized in that: The third fiber layer comprises third fibers and epoxy resin; the third fibers are selected from one or more of carbon fibers, glass fibers, modified carbon fibers, and polyimide fibers.

7. The crack-resistant baseball bat according to claim 1, characterized in that: The first isolation layer and the second isolation layer are BOPP.

8. The crack-resistant baseball bat according to claim 1, characterized in that: The composite adhesive film layer comprises the following raw materials in parts by weight: 75-115 parts of resin, 20-50 parts of rubber, 4-9 parts of curing agent, 2-15 parts of auxiliary agent, 1-7 parts of silane coupling agent, and 0.1-1 parts of carbon fiber powder; the resin is selected from one or more of bisphenol A epoxy resin, p-aminophenol epoxy resin, and diglycidyl isophthalate.

9. A process for producing a crack-resistant baseball bat according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, wrapping the modified carbon fiber impregnated with resin slurry on a core mold to obtain a first fiber layer; S2, wrapping the first fiber layer in sequence with a first isolation layer, a second fiber layer, a second isolation layer, a third fiber layer, and a composite adhesive film layer to obtain a preform; S3, curing the preform, demoulding from the core mold, and obtaining a crack-resistant baseball bat.

10. The process according to claim 9, characterized in that: In the above-mentioned S3, the curing treatment includes first treating at a temperature of 80-100° C. and a pressure of 8-10 MPa for 5-10 min, and then treating at a temperature of 140-150° C. and a pressure of 10-12 MPa for 35-40 min.